2018
DOI: 10.4103/ajns.ajns_195_17
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of decompressive craniectomy in traumatic closed head injury

Abstract: Objective:The aim of the current study was to observe functional outcomes of patients undergoing decompressive craniectomy (DC) for raised intracranial pressure (ICP) after blunt head injury and to assess possible predictive factors.Methodology:This study was a prospective cohort study which was conducted at Aga Khan University Hospital, Karachi over a period of 2 years (January 2015–December 2016). Adult patients, aged between 15 and 65 years of both genders undergoing DC during the study period were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Comparative to our study many studies report, younger age as a determinant of favorable outcomes than the older age, though the age cut off limits are heterogeneous among studies [12][13][14]. Similarly, good pupillary reaction is a significant predictor of favorable outcomes in our study as well in other published studies [10,14,15].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Comparative to our study many studies report, younger age as a determinant of favorable outcomes than the older age, though the age cut off limits are heterogeneous among studies [12][13][14]. Similarly, good pupillary reaction is a significant predictor of favorable outcomes in our study as well in other published studies [10,14,15].…”
Section: Discussionsupporting
confidence: 51%
“…Performing tracheostomy has not shown any association on outcome in our study. However Laghari et al has reported tracheostomy as a negative predictor of good functional outcome [13]. Saade et al has reported that having multiple lesions on CT results in poor outcomes compared to presence of a single lesion [10].…”
Section: Discussionmentioning
confidence: 99%
“… 13 16 22 23 24 Unfavorable outcomes reported were low-GCS scores on admission, postoperative hydrocephalus, tracheostomy, sphenoid fractures, and unchanged ICP. 21 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…DC-relatedmortality rates ranged from 12 to 55%. 16 20 21 22 24 25 26 27 In-hospital mortality rates ranged between 32 to 55%, 20 21 26 whereas 30-day mortality rates ranged from 12 to 28.3%. 16 22 24 27 Laghari et al reported an in-hospital mortality rate of 25% at 3 months in their series.…”
Section: Discussionmentioning
confidence: 99%
“…1 The mortality and morbidity are high and the percentage of patients that either die or survive with severe disability following severe traumatic brain injury is approximately 60%. 2,3 The mortality and morbidity remains very high even in the USA and Europe and even in centers that specialize in neurotrauma management and reaches upto atleast 50% even in such specialized neurotrauma centers. 1 The burden of severe traumatic brain injury is biggest in low and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%